OsWRKY76 positively regulates drought stress via OsbHLH148-mediated jasmonate signaling in rice - Zhang, Mingxing; Zhao, Ranran; Huang, Kai; Wei, Zhiqi; Guo, Boya; Huang, Shuangzhan; Li, Zhao; Jiang, Wenzhu; Wu, Tao; Du, Xinglin (Frontiers in Plant Science, 2023)
Drought stress is a major environmental threat that limits plant growth and crop productivity. Therefore, it is necessary to uncover the molecular mechanisms behind drought tolerance in crops. Here, OsWRKY76 positively regulated drought stress in rice. OsWRKY76 expression was induced by PEG treatment, dehydration stress, and exogenous MeJA rather than by no treatment. Notably, OsWRKY76 knockout weakened drought tolerance at the seedling stage and decreased MeJA sensitivity. OsJAZ12 was significantly induced by drought stress, and its expression was significantly higher in OsWRKY76-knockout mutants than in wild-type ZH11 under drought stress. Yeast two-hybrid and bimolecular fluorescence complementation assays showed that OsWRKY76 interacted with OsJAZ12. OsWRKY76 weakened the interaction between OsbHLH148 and OsJAZ12 in yeast cells. The OsJAZ12 protein repressed the transactivation activity of OsbHLH148, and this repression was partly restored by OsWRKY76 in rice protoplasts. Moreover, OsDREB1E expression was lower in OsWRKY76-knockout mutants than in wild-type ZH11 under drought stress, but it was upregulated under normal growth conditions. Yeast one-hybrid, electrophoretic mobility shift, and dual-luciferase assays showed that OsWRKY76 and OsbHLH148 bound directly to the OsDREB1E promoter and activated OsDREB1E expression in response to drought stress. These results suggest that OsWRKY76 confers drought tolerance through OsbHLH148-mediated jasmonate signaling in rice, offering a new clue to uncover the mechanisms behind drought tolerance.